Digital Humanities, Corpus and Language Technology = Humanidades Digitales, Corpus y Tecnología del Lenguaje A look from diverse case studies = Una mirada desde diversos casos de estudio - Grajales Ramírez, Andrés Felipe; Molina Mejía, Jorge Mauricio; Valdivia, Pablo (Data Science, Culture and Social Change, 2023)
"Digital Humanities, Corpus and Language Technology: A look from diverse case studies is an outstanding collection of research contributions that explores the intersection of technology and the humanities. The authors provide a comprehensive overview of how these technologies can enhance research across various disciplines, from literature to history to anthropology. This book is a mustread for anyone interested in future research in the humanities. Digital Humanities, Corpus, and Language Technologies are rapidly growing fields that have the potential to revolutionize research across various disciplines. New technologies have opened up new perspectives for research, allowing scientists to analyze data in previously impossible ways. The interdisciplinary approach and practical applications make it an invaluable resource for researchers, students, and anyone interested in the intersection of technology and the humanities."